Budgeting Costs and Returns for Indian River Citrus Production, 2003-04 - Ronald P. Muraro; John W. Hebb (EDIS)
Budget analysis provides the basis for many grower decisions. Budget analysis can be used to calculate potential profits from an operation, to determine cash requirements for an operation, or to determine break-even prices. This report presents a budget constructed from current data and serves as a format for growers to analyze costs and returns from their individual records. Estimated costs and returns of growing seedless grapefruit in the Indian River area of Florida are presented for the twentieth year. The format presented may be used by individual growers to budget costs and returns, utilizing individual data on specific groves. September 2004.